Application of Steady-State Integral Proportional Integral Controller for Inner Dynamics Control Loop of Multi-rotor UAVs - Tai, Jun Jet; Phang, Swee King; Hoo, Choon Lih (International Conference on Computing, Communication and Automation (Online), 2018)
The industry usage for racing grade multi-rotors have not yet been widely probed. These multi-rotors focus on maximizing system actuation whilst minimizing system overshoot and oscillations. These systems usually employ cascaded PID control loops, and are generally largely tuned by hand. This paper presents a novel control method adapted from steady state integral methods derived from direct current motors in order to develop a new control scheme for racing grade multi-rotors. The performance of this controller was tested on a quad-rotor non-linear dynamic model simulator. The controller shows good robustness and performance which is evidenced from the very small magnitude error under the influence of disturbance, while making tuning intuitive and simple.